Growth, survival rate, and reproductive performance of two superior strains of the giant freshwater prawn (Macrobrachium rosenbergii) - Khasani, Ikhsan; Sopian, Asep; Anggraini, Fajar; Pamungkas, Wahyu (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
The high productivity and quality of the harvested prawn are the main objectives of the intensive giant freshwater prawn (GFP) culture. Therefore, the breeding program to create a superior strain of the prawn has been conducted in several countries to support prawn farming. The purpose of this study was to evaluate the productivity and female reproductive performance of the GFP superior strains, namely the selected GI Macro (GI) and Siratu (SR) in the three farming conditions. The GI has resulted from an individual selection program based on standard length and maturation level characters. The multi-location test was conducted in the grow-out phase for 90 days at the three locations based on altitude, namely low-lands (in Subang, 10-25 m above the sea level, asl), medium-lands (in Ciamis, 70-100 m asl), high-lands (in Kuningan, 700-800 m asl). The growth characters consisting of total length/TL, standard length/SL, and body weight/BB of GI and SR were not significantly different, both on the Low, medium, and high lands ponds. The survival rate of the GI (87,3±7.26%) was significantly higher than the SR (71.0±0.08%) in the medium-land pond. In the high-lands pond, the survival rate of the SR (72.33±0.32%) was significantly higher than the GI (55.8±6.27%). Meanwhile, the productivity and percentage of the gravid female in the low-lands pond were not significantly different. The data suggested that the selected GI Macro is a location-specific genotype, more suitable to be cultured in the low and moderate-lands pond with warm temperature characteristics. Keywords: freshwater prawn, growth, multi-location, reproduction